Analysis of Kalam Nahy in Qur’an Surah Al-Isra Verse 36 Regarding the Ethics of Artificial Intelligence (AI) Usage - Muariva Muzakkir; Andi Miswar; Mardan (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2026)
The use of artificial intelligence (AI) is becoming increasingly widespread and is being applied in various aspects of modern life. The use of AI requires moral awareness and a critical mindset to ensure that users are not easily influenced by information from unclear or unverifiable sources. This study aims to analyze the kalam nahy in the Qur’an, Surah Al-Isra’ verse 36, and examine its relevance to the ethics of Artificial Intelligence (AI) usage. This type of research uses a qualitative approach, specifically a literature review (library research) with a descriptive analysis method. The findings indicate that Surah Al-Isra’ verse 36 prohibits following something without a clear and valid basis of knowledge. This verse emphasizes the importance of tabayyun, caution, and responsibility in receiving and disseminating information. In the context of AI use, these values can serve as ethical guidelines to ensure that technology is used wisely, critically, and in accordance with Islamic moral principles.